Envelhecimento e performatividade dos corpos travestis - Maziero, Bruna Rodrigues (2017)
That research has as objective understands the body representations and transvestites' ageing that act in different professions in a city of the interior of RS, what deserves prominence, for forming a social group of high vulnerability. Like this, little it is known on the ageing process and body of them, starting from their own representations. The methodological transport of the work was guided by the qualitative approach, and for production of the research sources, the technique of interviews was used in depth. It was noticed, starting from that research, that the transvestites build along their lives, a body performative, breaking the duality of the heteronormativity, that body, it is represented by them, as a place of production of social relationships with the other. On the ageing, there is concern with the possibility of they age alone, without family and/or companions, without financial stability and there is still the fear of the loss of the young body. However, there is no interest in exhaust the researched theme, nor reach categorical conclusions, but to make possible the enlargement of the discussion.